Caracterização de bacilos gram-negativos resistentes a carbapenêmicos isolados durante a pandemia de COVID-19 e fatores clínicos associados ao desfecho - Santana, Brunela (2023)
Patients with COVID-19 are at risk of being affected by secondary infections caused by Gram-negative bacilli, such as K. pneumoniae, P. aeruginosa, and A. baumannii. Beta-lactam antibiotics are used to treat these GNBs, but with the advent of antimicrobial resistance, treatment becomes increasingly difficult. In this scenario, polymyxins are reintroduced to treat GNB infections in critically ill patients. The severity of the patient's condition with COVID-19 associated with a secondary infection with multidrug-resistant GNB can strongly impact the patient's outcome. Thus, we aimed was to characterize carbapenem-resistant Gram-negative bacilli (BGN-RC) isolated in the second year of the COVID-19 pandemic at Hospital Estadual Dr. Jayme dos Santos Neves; define the clinical and demographic profile of patients from whom carbapenem-resistant K. pneumoniae was isolated and determine the risk factors associated with resistance to polymyxin B. Carbapenemresistant GNBs were collected during the second year of the pandemic for antimicrobial susceptibility testing and phenotypic and genetic analyses of resistance mechanisms. The clinical and demographic data of the study patients were obtained from the hospital's electronic medical record. A total of 376 samples of carbapenemresistant GNBs were collected between August 2021 and February 2022. All GNBs were categorized as multidrug-resistant (MDR). More than half of the K. pneumoniae isolates (51%) were resistant to polymyxin B. The majority of A. baumannii (62%) and P. aeruginosa (70%) isolates showed an MIC at the cutoff point of 2g/mL for polymyxin B. K. pneumoniae samples showed a prevalence of serine carbapenemase. In GNB samples, the blaKPC gene was prevalent in K. pneumoniae and P. aeruginosa, and blaOXA-23 was prevalent in A. baumannii. The most frequent comorbidities in patients from whom GNBs were isolated were arterial hypertension and diabetes mellitus and those aged over 60 years. Up to five comorbidities were observed in the same patient. Patients who died ended up spending less time in the hospital, probably as a result of associated comorbidities. Coinfections increased hospital stays and up to six pathogens occurred in the same patient. Patients exposed to polymyxin B-resistant KPRC were at increased risk of using more than 8 antimicrobials and developing co-infection with Candida sp. during the period of hospitalization in the ICU, regardless of whether or not they were positive for COVID19. The longer the hospitalization, the greater the number of antimicrobials prescribed for patients with COVID-19, especially meropenem, vancomycin, ceftriaxone, polymyxin B, and the antifungals micafungin and fluconazole.